2018
DOI: 10.1016/j.ultsonch.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and ultrasound-assisted synthesis of poly(vinyl chloride)/riboflavin modified MWCNTs: Examination of thermal, mechanical and morphology properties

Abstract: This study focused on the preparation and investigation of physicochemical features of new poly(vinyl chloride) (PVC) nanocomposites (NCs) including different amounts of carboxylated multi-walled carbon nanotubes (MWCNTs-COOH) functionalized with riboflavin (RIB). Firstly, to increase the hydrophilicity of MWCNTs, the surface of them was functionalized by incorporating and formation of ester groups with RIB as a low cost and environmentally friendly biomolecule through ultrasound and microwave irradiations. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In this work, due to the existence of AS moiety in the polymer structure, the MWCNTs were functionalized with aspartic acid (AS) as a bio-based molecule to improve interfacial interactions between the latter and former. Functionalization was done under microwave heating using a simple and low-cost method via formation of amide linkages between COOHs of MWCNTs and NH 2 of AS (Scheme S5) [38,39,59].…”
Section: Functionalization Of Mwcntsmentioning
confidence: 99%
“…In this work, due to the existence of AS moiety in the polymer structure, the MWCNTs were functionalized with aspartic acid (AS) as a bio-based molecule to improve interfacial interactions between the latter and former. Functionalization was done under microwave heating using a simple and low-cost method via formation of amide linkages between COOHs of MWCNTs and NH 2 of AS (Scheme S5) [38,39,59].…”
Section: Functionalization Of Mwcntsmentioning
confidence: 99%
“…In the literature, a favorably combined effect of microwave and ultrasound treatments on nanoparticle formation has been recently discussed and reported. [ 40–49 ] However, experimental studies and comparative analyses on whether hybrid microwave and ultrasound should be sequentially or simultaneously performed are very scarce. This work, therefore, aims to investigate the effect of ultrasound treatment in both consecutive and concurrent models on the bubble and particle sizes during and after the microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…They found that, for PPTA-ECH-MWNTs-NH2-x/PVC, mechanical properties were highly modified in comparison to pure PVC. Amir Abdolmaleki et al [30] have investigated the physicochemical features of PVC/MWCNTs functionalized with riboflavin (RIB). Their results conclude that there is a higher mechanical and thermal behavior for 12wt% PVC/(RIB) MWCNTs compared to other concentrations of MWCNTs.…”
Section: Introductionmentioning
confidence: 99%